2018
DOI: 10.31557/apjcc.2018.3.1.1
|View full text |Cite
|
Sign up to set email alerts
|

mRNA Biomarkers for Detection of Oral Squamous Cell Cancer

Abstract: Objectives: Cancer is one of the main causes of death in the world. Changes in the expression of CK19 and CEA genes in peripheral blood of OSCC patients were examined for early diagnosis. Methodology: The participants were 36 patients and 36 normal individuals. CK19 and CEA of blood serum were measured through Real-Time PCR. The relationship of the biomarkers with tumor staging and cancer development was examined. Results: Comparison of the two groups of participants using t-test indicated no significant diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…One such study shows a positive expression of CEA mRNA marker and CK19 mRNA marker in OSCC cases. The difference was significant between the patients and normal groups (Rashid et al, 2018).…”
Section: Discussionmentioning
confidence: 79%
“…One such study shows a positive expression of CEA mRNA marker and CK19 mRNA marker in OSCC cases. The difference was significant between the patients and normal groups (Rashid et al, 2018).…”
Section: Discussionmentioning
confidence: 79%
“…Discovering and identifying biomarkers associated with abortion can be an effective aid in diagnosing and preventing complications (36). Among the known biomarkers, microRNAs have high potential (36,37). Diagnosis based on molecular changes and changes in the expression of microRNAs that are altered in miscarriage can be beneficial in identifying or preventing people who are prone to miscarriage.…”
Section: Resultsmentioning
confidence: 99%
“…Cells transfected with miR-409-3p mimics showed a significant increase in MicroRNA expression compared to the negative control oligonucleotide group (P<0.20). Furthermore, as a result of this, there is a significant suppression of proliferation ability, indicating that miR-409-3p has the effect of inhibiting tumor growth (Ursu et al, 2020;Rashid et al, 2018). Additionally, flow cytometry along with supplement V/PI double staining showed that after increasing the level of miR-409-3p it significantly suppresses cancer cells, Compared to cells transfected with the control group, the proportion of total cell apoptosis also increased.…”
Section: The Role Of Mir-409-3p In Transfected Cellsmentioning
confidence: 90%